Electromechanical responses of optical fibers with piezoelectric coatings - Shiah, Yui-Chuin; Huang, Chien-Hsin; Huang, Jin H. (Journal of the Chinese Institute of Engineers, 2006)
This article presents the analysis for the electromechanical responses of optical fibers coated with piezoelectric materials. The piezoelectric coatings, functioning as sensors or actuators, have potentials in the development of novel acousto-optic devices. Despite the growing demand for optical fibers coated with piezoelectric materials, the research on their integrated system electromechanical responses still remains largely unexplored. The present study focuses on doubly clad optical fibers that are commonly commercially used. By use of Hamilton's principle applied to piezoelectric fundamentals, we successfully solve the governing equations for piezoelectric coatings polarized in the radial direction. Using the derived analytical formulations, numerical examples are investigated for direct and converse effects of such integrated optical fibers.